Immediate and late benefits of treating very elderly people with hypertension: results from active treatment extension to Hypertension in the Very Elderly randomised controlled trial. (4th January 2012) - Beckett, N; Peters, R; Tuomilehto, J; Swift, C; Sever, P; Potter, J; McCormack, T; Forette, F; Gil-Extremera, B; Dumitrascu, D; Staessen, J A; Thijs, L; et al.
Abstract : Objective To assess if very elderly people with hypertension obtain early benefit from antihypertensive treatment. Design One year open label active treatment extension of randomised controlled trial (Hypertension in the Very Elderly Trial (HYVET)). Setting Hospital and general practice based centres mainly in eastern and western Europe, China, and Tunisia. Participants People on double blind treatment at the end of HYVET were eligible to enter the extension. Interventions Participants on active blood pressure lowering treatment continued taking active drug; those on placebo were given active blood pressure lowering treatment. The treatment regimen was as used in the main trial—indapamide SR 1.5 mg (plus perindopril 2-4 mg if required)—with the same target blood pressure of less than 150/80 mm Hg. Main outcome measures The primary outcome was all stroke; other outcomes included total mortality, cardiovascular mortality, and cardiovascular events. Results Of 1882 people eligible for entry to the extension, 1712 (91%) agreed to participate. During the extension period, 1682 patient years were accrued. By six months, the difference in blood pressure between the two groups was 1.2/0.7 mm Hg. Comparing people previously treated with active drug and those previously on placebo, no significant differences were seen for stroke (n=13; hazard ratio 1.92, 95% confidence interval 0.59 to 6.22) or cardiovascular events (n=25; 0.78, 0.36 to 1.72). Differences were seen for total mortality (47 deaths; hazard ratio 0.48, 0.26 to 0.87; P=0.02) and cardiovascular mortality (11 deaths; 0.19, 0.04 to 0.87; P=0.03). Conclusion Very elderly patients with hypertension may gain immediate benefit from treatment. Sustained differences in reductions of total mortality and cardiovascular mortality reinforce the benefits and support the need for early and long term treatment. Trial registration Clinical trials NCT00122811 .